Phenomenon-based Learning and 5W1H question techniques for Developing Analytical Thinking Ability and Science Learning Achievement of Elementary Grade 4 Student - waedolah, souybah; คงชะวัน กิตติธัช; เวชวิริยะสกุล พัศรเบศวณ์ (Al-HIKMAH Journal, 2024)
The objectives of this research were 1) to compare pre-post-analytical thinking ability after learning by using phenomenon-based learning (PhBL) and 5W1H question technique, 2) to compare pre-post science achievement of learning by using phenomenon – based learning and 5W1H question technique, and 3) to examine student satisfaction with phenomenon-based learning and 5W1H question techniques. The population group was the grade 4 students under the Tessaban Mueang Pattani education division, 2nd semester, academic year 2023. The sample group used in the research were grade 4 students at the Tessaban 5 School, Tessabanmuangpattani, under the Pattani Municipality Education Department, room 4/1. The sample size was 29 people, and the sample group was obtained by cluster sampling using the classroom was a random unit. The tools used in the research were: 1) 4 plans for learning management using phenomenon-based learning and 5W1H question technique, 16 hours, 2) analytical thinking ability tests, 3) a science learning achievement tests, and 4) a questionnaire on satisfaction with phenomenon-based learning management and 5W1H question technique. Statistics used include mean, standard deviation, and dependent t-test. The research findings revealed that: 1) Students who received phenomenon-based learning and 5W1H question technique, had higher analytical thinking ability after learning than before learning, with statistical significance at the .05 level. 2) Students who received phenomenon-based learning management together with 5W1H question technique, had significantly higher academic achievement in science subjects after studying than before studying at the .05 level. 3) Students were at the highest level of satisfaction with the phenomenon-based learning management together with the 5W1H question technique.